2016
DOI: 10.1371/journal.pone.0167894
|View full text |Cite
|
Sign up to set email alerts
|

Natural Endogenous Human Matriptase and Prostasin Undergo Zymogen Activation via Independent Mechanisms in an Uncoupled Manner

Abstract: The membrane-associated serine proteases matriptase and prostasin are believed to function in close partnership. Their zymogen activation has been reported to be tightly coupled, either as a matriptase-initiated proteolytic cascade or through a mutually dependent mechanism involving the formation of a reciprocal zymogen activation complex. Here we show that this putative relationship may not apply in the context of human matriptase and prostasin. First, the tightly coupled proteolytic cascade between matriptas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Recent studies indicated that prostasin mediates matriptase activation both enzymatically and nonenzymatically [ 25 ], whereas this prostasin function in matriptase zymogen activation is limited to those cells with exogenous expression of matriptase and prostasin [ 26 ]. Thus, increased prostasin may contribute to matriptase activation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies indicated that prostasin mediates matriptase activation both enzymatically and nonenzymatically [ 25 ], whereas this prostasin function in matriptase zymogen activation is limited to those cells with exogenous expression of matriptase and prostasin [ 26 ]. Thus, increased prostasin may contribute to matriptase activation.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed functional relationships include one involving a reciprocal activator-substrate interaction between matriptase and prostasin and another involving potent inhibition of matriptase and prostasin by HAI-1 and HAI-2. Our previous studies, however, suggested that though they may be correct in some contexts these proposed functional linkages can not be generalized and are somewhat tissue-selective or context-dependent [ 11 , 17 , 18 ]. In the current study, the context-dependent nature of any functional relationship is further supported by the distinct pattern of zymogen activation observed in human skin samples, in which prostasin is activated at high levels primarily in the granular layer whereas matriptase zymogen activation occurs at much lower levels predominantly in the cells of the basal layer.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, the prostasin mAb YL89 did not detect the prostasin zymogen protein band in 184 A1N4 cell lysates ( Fig 1A , lane 3), and only a very weak band was seen in this area with HaCaT cell lysates. Upon induction of matriptase and prostasin zymogen activation by transiently exposing the cells to a pH 6.0 buffer, a proportion of the prostasin zymogen was converted to activated prostasin, which forms a stable 100-kDa complex with HAI-1 [ 7 , 17 ]. The 100-kDa activated prostasin complex can be detected by the total prostasin mAb YL11 ( Fig 1 , lanes 2, indicated by *) and by the activated prostasin mAb YL89 ( Fig 1 , lanes 4, indicated by *).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations